Application of Visual Distraction Diversion in An.G with Acute Lymphoblastic Leukemia (ALL) in Reducing Acute Pain Levels at the RSPAD Gatot Soebroto Hospital - rahayu maharani (JOURNAL EDUCATIONAL OF NURSING(JEN), 2023)
Pediatric nurses play a crucial role in reducing acute pain levels in children with Acute Lymphoblastic Leukemia (ALL) through the implementation of visual distraction techniques. This case study aims to describe the use of visual distraction in reducing acute pain levels in a specific case of a 7-year-old child, An.G, who has ALL. The study design is descriptive, focusing on implementing visual distraction (watching) as an intervention for children with ALL. The case study involves an intensive nursing assessment of the child with ALL. The primary focus is to provide visual distraction as a means of pain management. The results showed a notable decrease in the child's FLACC score to 3, indicating improved comfort. In conclusion, the application of visual distraction proved to be effective in managing acute pain in children with ALL.